Triterpenols in mangrove sediments as a proxy for organic matter derived from the red mangrove (Rhizophora mangle) - Koch, Boris Peter (2011)
Mangroves are the dominant type of vegetation along many tropical coasts. Organic matter (OM) derived from mangrove leaf litter and root material is stored in sediments and is a major contributor to the amount and chemical composition of sedimentary OM. A set of organic biomarkers in sediments was applied as a palaeo-indicator for the Holocene dynamics of a mangrove Estuary (Rio Caeté, Pará, Brazil). Six sediment cores were collected perpendicular to the present coast line and analysed for triterpenols and sitosterol. The influence of microbial biomarker degradation was implemented from a previous study. Biomarker profiles were validated with pollen data and multivariate statistics to test whether these compounds were suitable indicators for the palaeo-vegetation. Sediments deposited up to 2 Ma BP showed biomarker assemblages similar to those of recent surface sediment. In two cores, the biomarker composition revealed a transition from marsh to mangrove vegetation. Taraxerol, germanicol and b-amyrin provided the most significant chemotaxonomical information and, especially in combination, served as reliable proxies for OM from Rhizophora mangle in northern Brazil. The maximum age of the mangrove system ranged between 1000 and 5100 yr depending on the topographic elevation of the drilling location.